I Remember How We All Felt: Perceived Emotional Synchrony through Tourist Memory Sharing. (November 2020) - Wood, Emma H.
Durkheim's theory of collective emotion and the concept of perceived emotional synchrony are used to explore tourism memories and to create a conceptual model explaining how and why we come to agree on how we felt when reliving past tourism experiences. This process is dependent on the malleability of memory, which allows emotional synchrony to happen in retrospect, regardless of actual feelings at the time. I argue that the innate motivations behind this post-consumption merging are a stronger sense of community and of belonging to a social group. For tourism practitioners, this highlights where the true value lies for the consumer, the belief in a shared emotional experience. This value develops through the synchronization of memories creating the basis for a shared memory economy . The implications for tourism marketers are discussed, and suggestions for further research into memory and travel experience are identified.